Avian Haemosporidians in Greater Scaup (Aythya marila) and Lesser Scaup (Aythya affinis) from Wisconsin - Sarah A. Orlofske; Gina M. Magro; Jeffrey A. Bell; Vasyl V. Tkach; Bruce Urben; Robert C. Jadin (Journal of Parasitology, 2024)
Avian haemosporidians are a diverse group of protozoan parasites that infect a wide range of host species. Waterfowl are an ecologically and economically important group of hosts that have been underrepresented in studies of haemosporidians. Diving ducks have unique life history traits, and morphological, behavioral, and dietary differences separate them from more common dabbling ducks. Greater scaup (Aythya marila) and lesser scaup (Aythya affinis) are closely related diving ducks with declining population trends in North America. To better understand the diversity of haemosporidians within diving ducks and factors related to host infections in scaup, we surveyed 82 hunter-donated waterfowl from 8 species of divers, sea ducks, and dabblers from Green Bay, Wisconsin from 2019 to 2021. We used molecular detection methods and phylogenetic and statistical analyses to describe the diversity, host associations, and prevalence of haemosporidians. We detected 14 unique genetic lineages of haemosporidians, including 4 novel lineages. We identified at least 1 lineage of haemosporidian in each of the 8 host species of divers, sea ducks, and dabblers examined. Lesser scaup had more diverse haemosporidian communities than did greater scaup, but lineages showed no clustering among these hosts when incorporated in phylogenetic analyses with lineages from other Nearctic waterfowl. Female lesser scaup had the highest infection prevalence, but there was no effect of host age or year of sampling. Our findings underscore the importance of species and sex differences that could lead to a higher risk of infections. Our results also fill an important geographical sampling gap for haemosporidians along a key migratory route. Increased monitoring of haemosporidians in waterfowl could contribute to insights into parasite evolution and ecology and the conservation and management of host populations.